Effect of bariatric surgery before pregnancy on the vascular function in the offspring: protocol of a cross-sectional follow-up study - Karolien Van De Maele; Inge Gies; Roland Devlieger (BMJ Publishing Group, 2019)
Background The offspring of obese pregnant women are at risk for adverse metabolic, inflammatory and cardiovascular programming. Comprehensive long-term data are lacking on the contribution of changes in maternal weight after bariatric surgery before pregnancy compared with lifestyle interventions during pregnancy on the cardiovascular programming of the offspring.Methods EFFECTOR is designed as a cross-sectional cohort follow-up study targeting the children of different groups of women who were previously studied during their pregnancy. Four subgroups of children are identified, based on maternal weight characteristics during pregnancy: normal weight women, obese women without any intervention and obese women who underwent a lifestyle intervention during or bariatric surgery before pregnancy. Data collection is performed as a single study visit at home. Data on the sociodemographic situation, food habits and psychomotor development are obtained through questionnaires. During the home visit, extensive anthropometric and vascular assessment is performed. Information on body composition is provided by assessment of body weight and height, bioelectrical impedance analysis, skinfold measurements and ultrasound. Endothelial function is measured by non-invasive peripheral arterial tonometry (EndoPAT 2000). Biomarkers performed in blood and urinalysis conclude the data collection process.Trial registration number NCT02992106 (Pre-results).